The Effects of Gamified Learning Activities on English Learning Achievement of Grade 9 Students at Demonstration School of Suan Sunandha Rajabhat University - Laksanasut, Saharat; Seubsang, Pintipa; Ngiwline, Phuwitch (Journal of Modern Learning Development, 2021)
This study aimed to 1) compare the English learning achievement between the pre-test and post-test results of grade 9 students who engaged in gamified learning activities and 2) compare the English learning achievement of the experimental group that was taught through gamified learning activities to the controlled group that was taught through 2W3P based learning activities. The cluster random sampling was employed in this study and the participants were seventy-four grade 9 students studying in the 2nd semester of academic year 2020 at Demonstration School of Suan Sunandha Rajabhat University. The experiment was conducted for six weeks. The research instruments were 1. gamified lesson plans, 2. 2W3P based lesson plans, and 3. a learning motivation test. The statistical treatments to test the research’s hypothesis were paired sample t-test and t-test for independent sample. The study revealed that after employing the gamified learning activities, the experimental group’s learning achievement from the post-test was higher than the pre-test at .05 level of statistical significance, and the experimental group’s learning achievement from the post-test was higher than the learning achievement of the controlled group at .05 level of statistical significance.